Role and Responsibility of Notaries in Making Wills That Have the Potential to Violate Heirs' Rights Based on Islamic Inheritance Law in Jepara District - Purwanto, Purwanto (TABELLIUS: Journal of Law, 2025)
This study aims to determine and analyze the role and responsibility of Notaries in making wills that have the potential to violate heirs' rights based on Islamic inheritance law in Jepara District. This study uses an empirical juridical approach, the research specifications are descriptive qualitative, the data collection method for primary data is by interview and secondary data is by literature study, the data analysis method is descriptive analysis. Based on the results of the data analysis, it can be concluded that Jepara Notaries have a very large role and responsibility in preventing inheritance disputes in the Jepara area, namely that notaries must always educate heirs who wish to make a will so that in making the will they do not violate the maximum limit that may be bequeathed.